Challenges of Local Newspaper Sustainability in the Digital Era: Effect of Social Media Marketing on Customer Loyalty through Brand Image and Brand Awareness Development - Rosnaini Daga; Rukman Pala (UM Purwokerto Press, 2025)
This study aims to investigate the effect of social media marketing on customer loyalty with brand image and brand awareness as mediating variables. A survey approach with quantitative data was conducted among subscribers of Harian Berita in Ambon, Indonesia. The data were analyzed using Structural Equation Modeling with Partial Least Square (SEM-PLS). The results show that social media marketing has a positive impact on customer loyalty. When companies build and promote brand image and brand awareness through social media, it significantly enhances customer loyalty in the era of technological advancement. The study confirms that social media marketing positively influences customer loyalty both directly and indirectly through the development of brand image and brand awareness. These findings have important implications for the development of digital marketing strategies and brand excellence. Strengthening brand presence through social media can improve customer loyalty and contribute to increased company revenue in a competitive business environment.